Information Aggregation Through Costly Political Action - Lohmann, Susanne (American Economic Review, 1994)
Information about various policy alternatives is dispersed among the individual members of a society. Prior to a vote over the alternatives, some people take costly political action to signal their private information to voters. By informing voting decisions, political action has potential to decrease the likelihood that voters cast 'mistaken' votes. Perhaps surprisingly, preelection communication may be counterproductive. The dispersed information is partially aggregated by the vote and political action may contribute 'noise' to the voting process. In some cases, the voting mechanism is more likely to implement the full-information voting outcome in the absence of preelection political action. Copyright 1994 by American Economic Association.